2012
DOI: 10.1016/j.molimm.2012.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza rapidly induces antiviral genes in duck lung and intestine

Abstract: Ducks are the natural reservoir of influenza A and survive infection by most strains. To characterize the duck immune response to influenza, we sought to identify innate immune genes expressed early in an infection. We used suppressive subtractive hybridization (SSH) to construct 3 libraries enriched in differentially expressed genes from lung RNA of a duck infected with highly pathogenic avian influenza virus A/Vietnam/1203/04 (H5N1), or lung and intestine RNA of a duck infected with low pathogenic avian infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 60 publications
8
99
1
Order By: Relevance
“…Rapid cell death was found in an in vitro study were duck embryo fibroblast cells were infected with HPAI H5N1 (Kuchipudi et al, 2011), which may lead to a reduced number of virus-infected cells in ducks. Another study (Vanderven et al, 2012) describes the rapid induction of antiviral genes involved in antiviral defence and other cellular processes in the lung of H5N1 HPAI-infected ducks at 1 d.p.i. Our results appear to underline that the rapid induction of an inflammatory response in ducks together with a more rapid apoptotic response limits the replication of HPAI in the lungs of the duck.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid cell death was found in an in vitro study were duck embryo fibroblast cells were infected with HPAI H5N1 (Kuchipudi et al, 2011), which may lead to a reduced number of virus-infected cells in ducks. Another study (Vanderven et al, 2012) describes the rapid induction of antiviral genes involved in antiviral defence and other cellular processes in the lung of H5N1 HPAI-infected ducks at 1 d.p.i. Our results appear to underline that the rapid induction of an inflammatory response in ducks together with a more rapid apoptotic response limits the replication of HPAI in the lungs of the duck.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ISG58 expression was shown to be induced upon infection with influenza virus [4]. However, the exact roles of ISG58 in host defense have yet to be elucidated.…”
Section: Dear Editormentioning
confidence: 99%
“…However, for dsDNA binding, the C-terminal channel of ISG58 likely needs to undergo a conformational change, in which residues such as F284 and R294 would be exposed and contribute to the binding surface. ISG58 expression can be induced strongly upon viral infection [4], therefore, we sought to examine the potential inhibitory effect of ISG58 on viral replication by using a model of vesicular stomatitis virus expressing GFP (VSV-GFP). Earlier work reported that both ISG54 and ISG56 inhibited VSV replication when they were overexpressed in HEK293T cells [1,7].…”
Section: Dear Editormentioning
confidence: 99%
“…Previously we showed that MHC class I was upregulated in lung and intestine tissues of ducks infected with influenza (42). MHC class I clones were abundantly recovered following suppressive subtractive hybridization in lung tissues of ducks infected with highly pathogenic A/Vietnam1203/04 (H5N1) and in intestine of ducks infected with the low pathogenic A/British Columbia 500/ 2005 (H5N2).…”
Section: Discussionmentioning
confidence: 99%
“…Duck MHC class I clones were abundantly recovered in a subtractive hybridization to enrich for genes upregulated in influenzainfected tissues (42). To determine whether all MHC class I promoters are responsive to influenza-triggered innate immune signaling, a constitutively active duck RIG-I construct (31), which contains only the two caspase activation recruitment domains (CARDs), was used to drive the downstream signaling cascade.…”
Section: Mhc Class I Promoters Can Respond To Rig-i Signalingmentioning
confidence: 99%